How Evolution of Mutations Conferring Drug Resistance Affects Viral Dynamics and Clinical Outcomes of Cytomegalovirus-Infected Hematopoietic Cell Transplant Recipients - Springer, Kathryn L. (American Society for Microbiology, 2005)
Infection with cytomegalovirus (CMV) remains a significant cause of morbidity and mortality among hematopoietic cell transplant (HCT) recipients. We describe two pediatric HCT recipients who developed persistent and severe drug-resistant CMV infections. CMV resistance to foscarnet and ganciclovir was detected after only 6 and 11 weeks of therapy, respectively. Viral pol mutations associated with drug resistance in these patients included T838A (a novel mutation) and D588N, which were shown by marker transfer to confer foscarnet and multidrug resistance, respectively. Each of these mutations significantly reduced in vitro replication of CMV, suggesting that they may decrease viral fitness. This finding was further supported by the disappearance of mutations upon withdrawal of antiviral pressure in one patient. Novel antivirals or combination therapy may be required for the treatment of drug-resistant CMV in HCT recipients and perhaps in other severely immunocompromised patients.